2016
DOI: 10.1002/anie.201601156
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dynamic Assembly of Disulfide Macrocyclic Helical Foldamers with Remote Communication of Handedness

Abstract: Disulfide bridge formation was investigated in helical aromatic oligoamide foldamers. Depending on the position of thiol-bearing side chains, exclusive intramolecular or intermolecular disulfide bridging may occur. The two processes are capable of self-sorting, presumably by dynamic exchange. Quantitative assessment of helix handedness inversion rates showed that bridging stabilizes the folded structures. Intermolecular disulfide bridging serendipitously yielded a well-defined, C2 -symmetrical, two-helix bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 58 publications
(24 reference statements)
1
40
0
1
Order By: Relevance
“…Foldamer-based macrocycles raise questions about how the foldamer moieties interact when conned within a larger structure, and about how folding and macrocyclization affect each other. For example, Huc has demonstrated homochiral self-sorting in macrocycles of aromatic oligoamides, 21 and Chmielewski and Otto have very recently demonstrated a dynamic library that yields an emergent folding pattern. 22 In related work, Sawada and Fujita have used foldamers as the components of complex assemblies based on metal coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Foldamer-based macrocycles raise questions about how the foldamer moieties interact when conned within a larger structure, and about how folding and macrocyclization affect each other. For example, Huc has demonstrated homochiral self-sorting in macrocycles of aromatic oligoamides, 21 and Chmielewski and Otto have very recently demonstrated a dynamic library that yields an emergent folding pattern. 22 In related work, Sawada and Fujita have used foldamers as the components of complex assemblies based on metal coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules with helical structure have fascinated chemists for many years. Spiral staircases, 1 10 propellers, 11 , 12 and screws 13 are representative examples of helical structures that have attracted the attention of designers, architects and researchers. Chiral polycyclic aromatic compounds (PACs) have been of particular interest to fundamental researchers and material scientists since scientists became aware of correlations between molecular structure and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a significant difference in the environment for each unit. Such phenomena were also observed in other stapled foldamers . Decreasing the hydrocarbon crosslinking length from eight to five carbon atoms also results in a strong shielding of the amide, aromatic and ester protons.…”
Section: Resultsmentioning
confidence: 52%
“…Utilizing side‐chain crosslinking to reinforce conformational stability for helical aromatic foldamers has rarely been addressed . Very recently, Huc and co‐workers reported that stapled helical aromatic oligoamide could be achieved through disulfide‐bridging two side chains with the position being carefully chosen . Though yielding a considerable stabilization of the folded conformation, the stapling could not completely inhibit the P ⇄ M interconversion and the half‐life of helix inversion was measured to be 53 min in CDCl 3 at 30 °C.…”
Section: Introductionmentioning
confidence: 99%